Numerical Control Simulation and Experimental Study on End Milling Ordinary Cycloidal Gear in Five-axis CNC Machine Tool - Xu, Jianmin; Luo, Shanming; Chen, Shui xuan (Manufacturing Technology Journal, 2016)
A machining method of end milling cycloidal gear using ball end mill is proposed based on the analysis of grinding and side milling ordinary cycloid gear. The machining principle of end milling cycloid gear using 5-axis CNC milling machine is analyzed and the geometric model of end milling cycloid gear is established. At the same time the NC simulation of the machining process is conducted. End milling ordinary cycloid gear is conducted using five-axis machining center and it verifies the feasibility and scientific of end milling ordinary cycloidal gear. The machining precision of the cycloid gear is measured using a three coordinate measuring machine, and it verifies the reliability and usefulness of the machining method. It proves that the machining method can achieve grinding precision. Using end milling instead of grinding cycloid gear is achieved in order to improve the machining efficiency.
Keywords: ordinary cycloid gear; end milling; five-axis CNC machining; measuring accuracy